Efficacy, safety and prognostic factors analysis of first-line icotinib treatment in advanced non-small cell lung cancer patients with mutated EGFR - Huang, Aimi; Shen, Qing; Yu, Xiaolu; Wang, Huimin; Shi, Chunlei; Han, Baohui; Gu, Aiqin (Translational Cancer Research; Vol 7, No 3 (June 27, 2018): Translational Cancer Research, 2018)
Background: This study aimed to evaluate the efficacy, safety and prognostic factors of icotinib as first-line treatment in advanced non-small cell lung cancer (NSCLC) patients with epidermal growth factor receptor (EGFR)-sensitive mutation. Methods: A total of 152 advanced NSCLC patients with EGFR-sensitive mutation underwent first-line icotinib treatment were retrospectively reviewed in this cohort study. Icotinib was given orally three times daily at 125 mg dose. Scorpion amplification refractory mutation system kit was used for EGFR mutation detection. The median follow-up duration was 15.0 (range: 1.0–44.0) months, and the last follow-up date was 2016/12/31. Results: The complete response (CR), partial response (PR), objective response rate (ORR), stable disease (SD) and progressive disease (PD) rates were 4% (N=6), 67.8% (N=103), 71.8% (N=109), 23.7% (N=36) and 4.6% (N=7) respectively. Median progression-free survival (PFS) and overall survival (OS) were 14.0 months (95% CI: 12.7–15.3 months) and 33.0 months (95% CI: 24.9–41.1 months) respectively. Multivariate logistic analysis indicated smoking history (P=0.013) was statistically correlated with non-ORR achievement, while EGFR mutation 19del (P=0.001) was statistically associated with ORR achievement. No factor could predict PFS or OS. As to safety profiles, there were 66 (43.4%), 35 (23.0%), 10 (6.6%), 9 (5.9%), 9 (5.9%), 4 (2.6%) and 3 (2.0%) patients appeared rash, diarrhea, abnormal liver function, paronychia, oral ulcer, fatigue and poor appetite, and most adverse events (AEs) were in mild grade. Conclusions: First-line icotinib treatment was efficient and well tolerated in patients with advanced NSCLC harboring EGFR mutations, and smoking history was negatively while EGFR mutation 19del was positively correlated with ORR achievement.